Biotechnology for the production of Iris spuria L. plant material with a specified content of extractives. Issue 1 (January 2021) - Tikhomirova, L I; Ponomareva, J V
Abstract: The study was aimed at the establishment of stock plant material of Iris spuria L. (Art And Soul) through biotechnological methods and its primary phytochemical analysis. For the first time, a series of studies aimed at multiplying plant materials Iris spuria L. (Art And Soul) resulted in the development of culture media and cultivation schemes. In the stage of micropropagation as such, the most optimal content in culture media was found to be 2.5-5.0 µm BAP. To ensure a more complete realization of morphogenetic potentials, it is necessary to alternate phytohormone and hormone-free media. In this case, L-glutamine and adenine sulfate should be added to hormone-free media in the amount of 100 mg/l (MS+100 mg/l L-glutamine+100 mg/l adenine sulfate). Qualitative and quantitative compositions of extractives removed in a Soxhlet apparatus from the technological plant material of Iris spuria depends on the solvent polarity. The amount of extractives increases with accelerated solvent polarity (96% ethanol → 60% ethanol → water). In this case, phenols, condensed and hydrolyzable tannins, alkaloids, glycosides were extracted. The study proves the relationship between the accumulation of quercetin and the hormonal composition of culture media, which allows for the regulation of these polyphenols being accumulated in the production of the plant material of Iris spuria L. (Art And Soul).